ETHNIC ENTREPRENEURSHIP AND POST-SOVIET TRANSFORMATION OF KOREANS IN CENTRAL ASIA - Ashurova Ulgozi Isroilovna (Innovate Conferences, 2025)
Following the dissolution of the Soviet Union in 1991, the Korean diaspora in Central Asia faced a new challenge: adapting from the planned economy to the market system. This paper examines how Koreans in Kazakhstan, Uzbekistan, and Kyrgyzstan developed ethnic entrepreneurship models rooted in social trust, kinship, and cultural discipline. The analysis shows how traditional practices such as the kobonji (brigade-based semi-legal work structure) evolved into legitimate small and medium enterprises (SMEs) during the post-Soviet transition.
Keywords: Ethnic entrepreneurship; Koryo-saram; post-Soviet economy; Kazakhstan; Uzbekistan; social capital; kobonji system; diaspora networks; Confucian collectivism; small and medium enterprises.